A PON for All Seasons: Comparing Paraoxonase Enzyme Substrates, Activity and Action including the Role of PON3 in Health and Disease - Chrysan J. Mohammed; Sabitri Lamichhane; Jacob A. Connolly; Sophia M. Soehnlen; Fatimah K. Khalaf; Deepak Malhotra; Steven T. Haller; Dragan Isailovic; David J. Kennedy (MDPI AG, 2022)
Paraoxonases (PONs) are a family of hydrolytic enzymes consisting of three members, PON1, PON2, and PON3, located on human chromosome 7. Identifying the physiological substrates of these enzymes is necessary for the elucidation of their biological roles and to establish their applications in the biomedical field. PON substrates are classified as organophosphates, aryl esters, and lactones based on their structure. While the established native physiological activity of PONs is its lactonase activity, the enzymes' exact physiological substrates continue to be elucidated. All three PONs have antioxidant potential and play an important anti-atherosclerotic role in several diseases including cardiovascular diseases. PON3 is the last member of the family to be discovered and is also the least studied of the three genes. Unlike the other isoforms that have been reviewed extensively, there is a paucity of knowledge regarding PON3. Thus, the current review focuses on PON3 and summarizes the PON substrates, specific activities, kinetic parameters, and their association with cardiovascular as well as other diseases such as HIV and cancer.